Antibacterial activity of the novel compound Sudapyridine (WX-081) against Mycobacterium abscessus - Nie, Wenjuan; Gao, Shan; Su, Lei; Liu, Lina; Geng, Ruixue; You, Yingxia; Chu, Naihui (Frontiers in Cellular and Infection Microbiology, 2023)
Objective This study aimed to investigate sudapyridine (WX-081) antibacterial activity against Mycobacterium abscessus in vitro and its effect on in vivo bacterial growth and host survival using a zebrafish model of M. abscessus infection. Methods WX-081 in vitro antibacterial activity was assessed based on growth inhibition of M. abscessus standard strain ATCC19977 and 36 clinical isolates. Maximum tolerated concentrations (MTCs) of WX-081, bedaquiline, and azithromycin and inhibition of M. abscessus growth were assessed in vivo after fluorescently labelled bacilli and drugs were injected into zebrafish. Bacterial counts were analysed using one-way ANOVA and fluorescence intensities of zebrafish tissues were analysed and expressed as the mean ± SE. Moreover, Kaplan-Meier survival analysis was conducted to assess intergroup differences in survival of M. abscessus-infected zebrafish treated with different drug concentrations using a log-rank test, with a p value <0.05 indicating a difference was statistically significant. Results Drug sensitivity testing of M. abscessus standard strain ATCC19977 and 36 clinical isolates revealed MICs ranging from 0.12-0.96 µg/mL and MIC50 and MIC90 values of 0.48 µg/mL and 0.96 µg/mL, respectively. Fluorescence intensities of M. abscessus-infected zebrafish tissues was lower after treatment with the WX-081 MTC (62.5 µg/mL) than after treatment with the azithromycin MTC (62.5 µg/mL) and the bedaquiline MTC (15.6 µg/mL). When the concentration of WX-081 increased from 1.95µg/mL to 1/8 MTC(7.81µg/mL), the survival rate of zebrafish at 4-9 dpf decreased from 90.00% to 81.67%. Conclusion WX-081 effectively inhibited M. abscessus growth in vitro and in vivo and prolonged survival of M. abscessus-infected zebrafish, thus indicating that WX-081 holds promise as a clinical treatment for M. abscessus infection.